Granzyme B Gene Polymorphism Associated with Subacute Sclerosing Panencephalitis - BARIŞ, SAFA (GEORG THIEME VERLAG KG, 2014)
Background Subacute sclerosing panencephalitis (SSPE) is a late complication of measles infection. Immune dysfunction related to genetic susceptibility has been considered in disease pathogenesis. A functional single nucleotide polymorphism (SNP) of granzyme B gene (GZMB) reported in several pathologies may also be involved in susceptibility to SSPE. Patients and Methods An SNP (rs8192917, G -> A, R -> Q) was screened in 118 SSPE patients and 221 healthy controls (HC) by polymerase chain reaction-restriction fragment length polymorphism. Frequencies were compared between groups. In vitro production of GZMB was measured in controls with different genotypes. Results The SNP had a minor allele (G) frequency of 0.22 in patients and 0.31 in controls. GG genotype was significantly less frequent in patients (odds ratio, 0.23). G allele carriers produced relatively higher levels of GZMB, when stimulated in vitro. Conclusion These findings implicate possible effect of this genetic polymorphism in susceptibility to SSPE which needs to be confirmed in bigger populations.
Keywords: subacute sclerosing panencephalitis; granzyme B; single nucleotide polymorphism; function; MEASLES-VIRUS; ACTIVATION; APOPTOSIS; DISEASE; ALLELE; BRAIN; CELLS